SO2-resistant catalyst and preparation method thereof
By using TiO2 support materials and SO2-resistant catalysts with catalytically active components such as V2O5, the problem of deactivation of DeNOx catalysts in the prior art under low temperature and high SO2 environments is solved, and efficient NOx removal and catalytic performance improvements are achieved.
Patent Information
- Application Number
- CN202380040913.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-16
- Filing Date
- 2023-05-16
- Publication Date
- 2024-12-27
AI Technical Summary
The existing DeNOx catalysts are rapidly deactivated in low temperature and high SO2 environments, and the catalysts are insufficient in catalytic performance when used in filter bags, and cannot effectively remove NOx, dioxin and other pollutants in industrial flue gas.
Using SO2-resistant catalysts including TiO2 support materials and catalytically active components such as V2O5, prepared by dry mixing and heat treatment, ensuring that the catalyst has a high NOx removal efficiency in the range of 150°C to 280°C and reducing the initial inactivation rate in the presence of SO2.
It improves the stability and catalytic performance of the catalyst in low temperature and high SO2 environments, significantly improves the NOx removal efficiency and the SO2 tolerance of the catalyst, and extends the service life of the catalyst.
Smart Images

Figure CN119212785A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to U.S. Provisional Application No. 63 / 342,342, filed May 16, 2022, which is incorporated herein by reference in its entirety for all purposes. Technical Field
[0003] The present disclosure generally relates to SO 2 Supported catalysts, and methods of making supported catalysts. More specifically, the present disclosure relates to supported catalysts and methods of making supported catalysts by dry mixing and thermal treatment. Background Art
[0004] Conventional methods for producing supported catalysts generally include pellet or support preparation, liquid impregnation of the catalyst support in a solution containing a catalyst precursor, followed by a drying process to remove the liquid, and then a calcination process. The liquid impregnation and drying steps generally require more than five hours, and the calcination step performed after the liquid impregnation and drying may also require more than five hours.
[0005] In addition, some commercially available DeNOx catalysts (e.g., for removing NO and NO 2 For example, monolithic DeNOx catalysts and pelletized DeNOx catalysts need to be ground into smaller particles, while some commercial powdered DeNOx catalysts do not have sufficient catalytic activity, particle size distribution, shape or morphology to maximize catalytic performance in filter bag format.
[0006] Additionally, air pollution has become a major concern worldwide. In the past few years, many countries have issued stringent emission requirements to minimize NOx emissions. While DeNOx catalytic filter systems are generally known, they are often used in certain operating conditions that are prevalent in specific industries (e.g., industries that carry out processes at lower temperatures, or involve higher concentrations of SO 2 In industries with high CO2 emissions, such as cement production, rapid deactivation of the DeNOx catalyst may occur.
[0007] Therefore, it is necessary to have high SO 2 Tolerant low temperature selective catalytic reduction ("SCR") DeNOx catalysts and more efficient production methods for making these catalysts. There is also a need for improved methods of removing NOx compounds, dioxins and dioxin-like compounds, halogenated compounds and fine particulate matter from industrial flue gases, such as cement production plant flue gases. Summary of the invention
[0008] The present disclosure generally relates to SO 2 Catalyst and preparation for SO2 resistant2 A method of supporting a catalyst may include mixing a dry catalyst precursor including a metal and a ligand with a dry support material to form a mixture, and calcining the mixture.
[0009] According to a first embodiment ("Embodiment 1"), a catalyst is provided, the catalyst comprising a catalytically active component and a TiO 2 A carrier material having a crystal structure including an anatase phase. In some embodiments, the carrier material includes an auxiliary material.
[0010] Embodiment 2 is the catalyst as described in embodiment 1, wherein the auxiliary material is selected from SiO 2 、MoO 3 , WO 3 and Al 2 O 3 At least one of .
[0011] Embodiment 3 is the catalyst as described in embodiments 1-2, wherein the weight percentage of the auxiliary material is 2% to 35% based on the total weight of the catalyst, based on the total weight of the catalyst.
[0012] Embodiment 4 is the catalyst as described in embodiment 1-3, wherein the auxiliary material is SiO 2 .
[0013] Embodiment 5 is the catalyst as described in embodiment 1-4, wherein the peak intensity ratio [(Ia / Ib)×100] is 30% to 360%, and the peak intensity ratio [(Ia / Ib)×100] represents the peak intensity ratio of TiO 2 The ratio of the peak intensity [Ia] of anatase crystals existing in the range of 2θ=24.7° to 2θ=25.7° of the powder X-ray diffraction of the standard sample titanium dioxide composed of anatase to the peak intensity [Ib] of anatase existing in the range of 2θ=24.7° to 2θ=25.7° of the powder X-ray diffraction of the standard sample titanium dioxide composed of anatase.
[0014] Embodiment 6 is the catalyst of embodiment 1-5, wherein the catalyst has a NOx removal efficiency of 30% to 90% in a temperature range of 150°C to 280°C.
[0015] Embodiment 7 is the catalyst of embodiment 6, wherein the catalyst has a relative humidity of 40 to 400 cm-1 at a temperature range of 150° C. to 280° C. 3 The apparent reaction rate constant of / gs is used to 3 Selective catalytic reduction of NOx.
[0016] Embodiment 8 is the catalyst of embodiment 1-7, wherein the catalyst has a NOx removal efficiency of 60% to 80% in a temperature range of 170°C to 220°C.
[0017] Embodiment 9 is the catalyst as described in embodiment 1-8, wherein when in SO 2 In the presence of NH 3 When testing the selective catalytic reduction of NOx, the 2 Compared with the catalyst having the support material, the catalyst has a reduced initial deactivation rate.
[0018] Embodiment 10 is the catalyst of embodiment 1-9, wherein the specific surface area of the support material is 50 to 500 m 2 / g.
[0019] Embodiment 11 is the catalyst of embodiment 1-10, wherein the catalytically active component comprises at least one of the following: vanadium monoxide (VO), vanadium trioxide (V 2 O 3 ), vanadium dioxide (VO 2 ), vanadium pentoxide (V 2 O 5 ), molybdenum trioxide (MoO 3 ), manganese oxide (MnO 2 ), iron(III) oxide (Fe 2 O 3 ), iron (II) oxide (FeO), cupric oxide (CuO), or any combination thereof.
[0020] Embodiment 12 is the catalyst as described in embodiments 1-11, wherein the loading weight percentage of the catalytically active component is 4% to 50%, based on the total weight of the catalyst.
[0021] Embodiment 13 is the catalyst as described in embodiments 1-12, wherein the loading weight percentage of the catalytically active component is 10% to 30%, based on the total weight of the catalyst.
[0022] Embodiment 14 is the catalyst of embodiments 1-13, wherein the support material comprises particles having an average diameter of 0.5 μm to 1000 μm.
[0023] Embodiment 15 is the catalyst as described in embodiment 1-14, wherein the catalytically active component is V 2 O 5 , the carrier material is TiO 2 , the auxiliary material is SiO 2 .
[0024] Embodiment 16 is a catalytic article comprising the catalyst as described in embodiments 1-15.
[0025] Embodiment 17 is a catalytic reaction method comprising contacting a reactant stream with a catalyst as described in embodiments 1-15.
[0026] Embodiment 18 is the catalyst of claims 1-15 or the catalytic article of claim 16, wherein the catalyst or catalytic article has a NOx removal efficiency of 10% to 99% in the temperature range of 150°C to 280°C.
[0027] Embodiment 19 is a method of reducing an amount of a compound from a gas stream, comprising: providing a first gas stream having a first concentration of the compound, and contacting the gas stream with the catalytic article of embodiment 16 to form a second gas stream having a second concentration of the compound. In some embodiments, the first concentration is greater than the second concentration.
[0028] Embodiment 20 is the method of embodiment 19, wherein the first gas stream comprises SO at a concentration of 1 to 200 ppm. 2 .
[0029] Embodiment 21 is the method of embodiments 19-20, wherein the compound comprises NOx.
[0030] Embodiment 22 is a method as described in embodiments 19-21, wherein the compound includes nitrogen (N 2 ), at least one of dioxins or dioxin-like compounds, halogens or halogenated compounds.
[0031] Embodiment 23 is a method as described in embodiments 19-22, wherein the first gas stream further includes oxygen (O 2 ), water (H 2 O), carbon monoxide (CO), carbon dioxide (CO 2 ), sulfur dioxide (SO 2 ), sulfur trioxide (SO 3 ), hydrocarbons, or at least one of one or more organic or inorganic materials.
[0032] Embodiment 24 is a method as described in embodiments 19-23, wherein the gas flow is a flue gas flow with a temperature of 140 to 280°C.
[0033] Embodiment 25 is the method of embodiment 24, further comprising increasing the compound removal efficiency of the catalytic article, comprising: adding ammonia (NH4) in a concentration range of 0.0001% to 0.5% of the flue gas flow concentration; 3); and increasing the temperature of the flue gas flow to 240° C. to 280° C. In some embodiments, the compound may be NOx.
[0034] Embodiment 26 is a method as described in embodiment 24, wherein the method further includes increasing the compound removal efficiency of the catalytic article, including: introducing additional NO into the flue gas stream. 2 , change NO 2 The concentration is increased to between 2% and 99% of the total NOx concentration in the first gas stream.
[0035] Embodiment 27 is a method of preparing a catalyst, comprising mixing a catalyst precursor having a metal and a ligand with a support material to form a mixture, wherein the support material comprises TiO 2 ; calcining the mixture; and adding auxiliary materials to the support material to make TiO 2 The crystal structure remains essentially the same.
[0036] Embodiment 28 is a method as described in embodiment 27, wherein the metal is selected from one or more of transition metals, alkali metals or alkaline earth metals, or salts thereof.
[0037] Embodiment 29 is the method of embodiments 27-28, wherein the metal is selected from the group consisting of vanadium, molybdenum, copper, iron, or mixtures thereof.
[0038] Embodiment 30 is a method as described in embodiments 27-29, wherein the ligand is a carbonyl, oxalate, ammonium, cyclopentadienyl, diketonate or a ligand of formula I:
[0039]
[0040] wherein R1 and R2 are each independently alkyl, substituted alkyl, aryl, substituted aryl, acyl and substituted acyl.
[0041] Embodiment 31 is a method as described in embodiments 27-30, wherein the catalyst precursor is selected from the following group: vanadyl acetylacetonate, vanadium (III) acetylacetonate, bis (acetylacetonate) dioxomolybdenum (VI), iron (III) acetylacetonate and copper (II) acetylacetonate.
[0042] Embodiment 32 is a method as described in embodiments 27-31, wherein the metal content of the catalyst is 4 wt% to 50 wt%, based on the total weight of the catalyst.
[0043] Embodiment 33 is a method of preparing a catalyst, comprising: mixing a catalyst precursor comprising a metal and a ligand with a support material to form a mixture, and calcining the mixture. In some embodiments, the support material comprises TiO 2 and auxiliary materials, the TiO 2 It has a crystal structure including anatase phase.
[0044] Embodiment 34 is a method for preparing a catalyst, comprising: 2 Mixed with auxiliary materials to form TiO 2 The support material, the TiO 2 having a crystal structure including anatase phase; mixing a catalyst precursor including a metal and a ligand with the support material to form a mixture; and calcining the mixture.
[0045] Embodiment 35 is a method as described in embodiments 27-34, wherein the auxiliary material is selected from the group consisting of SiO 2 、MoO 3 , WO 3 and Al 2 O 3 .
[0046] The above embodiments are limited thereto and should not be construed as limiting or otherwise narrowing the scope of any inventive concept otherwise provided by the present disclosure. Although multiple embodiments are disclosed, other implementations will be apparent to those skilled in the art from the following detailed description showing and describing exemplary embodiments. Therefore, the drawings and detailed description are considered to be illustrative rather than restrictive in nature. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] The accompanying drawings are included to provide a further understanding of the present disclosure, and are incorporated in and constitute a part of this specification. The drawings illustrate embodiments of the present disclosure and together with the description serve to explain the principles of the present disclosure.
[0048] Figure 1 is a bar graph showing comparative data of NOx removal efficiency of various catalysts at different temperatures according to an embodiment;
[0049] Figure 2 is a line graph showing comparative data of apparent reaction rate constants of various catalysts at different temperatures, according to an embodiment;
[0050] Figure 3 According to an embodiment, two different catalysts are shown to react with SO 2 Line graph of relative NOx removal efficiency over time;
[0051] Figure 4According to an embodiment, two different catalysts are shown to react with SO 2 Histogram of initial inactivation rate over time;
[0052] Figure 5 According to the embodiment, various support materials and TiO 2 A graph of an X-ray diffraction pattern of a catalyst;
[0053] Figure 6 is a flow chart illustrating a method of reducing the amount of a compound in a gas stream, according to an embodiment;
[0054] Figure 7 is a flow chart illustrating a method of reducing the amount of a compound in a gas stream, according to an embodiment. DETAILED DESCRIPTION
[0055] Definitions and terminology
[0056] The present disclosure is not intended to be interpreted in a limiting manner. For example, the terms used in this application should be interpreted broadly in the context of the meanings given to such terms in the art.
[0057] For imprecise terms, the terms "about" and "approximately" are used interchangeably to indicate that a measurement includes the stated measurement and also includes any measurement that is reasonably close to the stated measurement. As understood and readily determined by a person of ordinary skill in the relevant art, a measurement that is reasonably close to the stated measurement has a fairly small deviation from the stated measurement. Such deviations may be due to measurement errors, differences in calibration of measurement and / or manufacturing equipment, human errors in reading and / or setting measurements, fine-tuning to optimize performance and / or structural parameters due to measurement differences associated with other components, specific implementation scenarios, imprecise adjustments and / or manipulation of objects by humans or machines, etc. If it is determined that a person with ordinary skill in the relevant art cannot easily determine the value of such a reasonably small difference, the terms "about" and "approximately" may be understood to mean plus or minus 10% of the stated value.
[0058] As used herein, the term "dioxin-like compounds" refers to polychlorinated dibenzo-p-dioxins ("PCDDs" or "dioxins"), polychlorinated dibenzofurans ("PCDFs" or "furans"), polychlorinated biphenyls ("PCBs"), or polybrominated analogs of dioxins, furans, and PCBs.
[0059] The term "NOx" refers to nitrogen oxides, such as NO or NO 2 .
[0060] The term "DeNOx catalyst" refers to a catalyst used to remove NOx, sometimes used in emissions control.
[0061] The term "apparent reaction rate constant (km )” can be calculated as follows:
[0062]
[0063] where k m The mass of the catalyst involved (cm 3 / gs) of the first-order apparent reaction rate, V is the gas flow rate under the reaction conditions (cm 3 / s), W is the catalyst mass (g). DeNOx efficiency is defined as follows:
[0064]
[0065] The apparent reaction rate constant is a measure of the amount of gas processed per unit time and mass of catalyst.
[0066] The term "selective catalytic reduction (SCR)" refers to a process in which NOx is converted into diatomic nitrogen and water with the aid of a catalyst. 3 ), ammonia solution (NH 4 OH) or urea (CO(NH 2 ) 2 ) solution) is added to the flue gas or exhaust gas flow and reacts on the catalyst. For example, in the SCR process of NOx, NH 3 It is introduced as a reducing agent and reacts with NOx on the surface of the DeNOx catalyst.
[0067] The term "relative DeNOx efficiency" refers to the ratio of the DeNOx efficiency at a given time in a deactivation cycle to the initial DeNOx efficiency of a fresh catalyst.
[0068] The term "initial deactivation rate" refers to the decrease in relative DeNOx efficiency over time.
[0069] Description of various embodiments
[0070] Those skilled in the art will readily appreciate that the various aspects of the present disclosure may be implemented by any number of methods and devices configured to implement the desired effects. It should also be noted that the drawings referenced herein are not necessarily drawn to scale, but may be exaggerated to illustrate various aspects of the present disclosure, and in this regard, the drawings should not be considered limiting.
[0071] The present disclosure generally relates to SO 2 Catalyst and preparation for SO2 resistant 2 A method of supporting a catalyst may include mixing a dry catalyst precursor including a metal and a ligand with a dry support material to form a mixture, and calcining the mixture.
[0072] In some embodiments, the catalyst may include a catalytically active component; and a TiO 2 The support material, the TiO 2 It has a crystal structure including anatase phase.
[0073] In some embodiments, the catalyst includes at least one catalytically active component. In some embodiments, the at least one catalytically active component includes at least one of the following: vanadium monoxide (VO), vanadium trioxide (V 2 O 3 ), vanadium dioxide (VO 2 ), vanadium pentoxide (V 2 O 5 ), tungsten trioxide (WO 3 ), molybdenum trioxide (MoO 3 ), manganese oxide (MnO 2 ), iron(III) oxide (Fe 2 O 3 ), iron (II) oxide (FeO), copper oxide (CuO), or any combination thereof. In some embodiments, the at least one catalytically active component comprises at least one of the following: vanadium monoxide (VO), vanadium trioxide (V 2 O 3 ), vanadium dioxide (VO 2 ), vanadium pentoxide (V 2 O 5 ) or any combination thereof. In an exemplary embodiment, the at least one catalytically active component comprises only V 2 O 5 .
[0074] In some examples, the carrier material includes an auxiliary material. In some embodiments, the auxiliary material may be SiO 2 ,Fe 2 O 3 ,CrO 3 ,Re 2 O 7 ,Nb 2 O 5 ,K 2 O,MoO 3 ,WO 3 ,Al 2 O 3 In one exemplary embodiment, the auxiliary material is SiO 2 .
[0075] In some embodiments, the support material has a crystalline structure having a [(Ia / Ib)×100] ratio of 30% to 360%, wherein the [(Ia / Ib)×100] ratio represents the ratio of the TiO 2 The ratio of the peak intensity [Ia] of anatase crystals existing in the range of 2θ = 24.7° to 2θ = 25.7° in the powder X-ray diffraction of the titanium dioxide of the standard sample composed of anatase to the peak intensity [Ib] of anatase existing in the range of 2θ = 24.7° to 2θ = 25.7° in the powder X-ray diffraction of the titanium dioxide of the standard sample composed of anatase. 2 It can be M311Hombikat TiO purchased from Venator 2 .
[0076] In some embodiments, the weight percentage of the auxiliary material is about 2 wt.% to about 35 wt.%, or about 3 wt.% to 30 wt.%, or about 4 wt.% to 25 wt.%, or about 5 wt.% to about 20 wt.%, or about 10 wt.% to about 15 wt.%, based on the total weight of the catalyst.
[0077] Figure 1 is a bar graph showing comparative data of NOx removal efficiency of various catalysts at different temperatures according to an embodiment. Figure 1 The data are calculated based on data collected during the Catalyst Evaluation Program1, which is discussed in further detail below.
[0078] As shown, the catalyst may have a catalytic activity of about 30% to about 90%, or about 40% to about 90%, or about 50% to about 90%, or about 60% to about 80%, or about 60% to about 80% in the temperature range of 150° C. to 250° C. More specifically, in the temperature range of 170° C. to 220° C., the catalytic activity of the catalyst may be about 60% to about 80%, or about 65% to about 80%, or about 70% to about 80%.
[0079] In some embodiments, the catalyst may exhibit catalytic activity in a temperature range of 150°C to 280°C, or about 152°C to 260°C, or 155°C to 240°C, or 160°C to 230°C, or 165°C to 225°C, or 170°C to 220°C, or 175°C to 220°C, or 175°C to 200°C.
[0080] For example, the catalyst may have a catalytic activity of about 30% to about 90% in a temperature range of 150°C to 250°C, or a catalyst may have a catalytic activity of 60% to 80% in a temperature range of 170°C to 220°C.
[0081] Figure 2is a line graph showing comparative data of apparent reaction rate constants of various catalysts at different temperatures, according to an embodiment. Figure 2 The data are calculated based on data collected during the Catalyst Evaluation Program1, which is discussed in further detail below.
[0082] As shown, the catalyst may have a NH3 selective catalytic reduction of NOx of about 40 to about 400 cm 3 / gs, or about 50 to about 350cm 3 / gs, or about 60 to about 300cm 3 / gs, or about 70 to about 250cm 3 / gs, or about 80 to about 220cm 3 / gs, or about 90 to about 200cm 3 / gs, or about 100 to about 180cm 3 / gs, or about 110 to about 160cm 3 / gs apparent reaction rate constant.
[0083] Figure 3 According to an embodiment, two different catalysts are shown to react with SO 2 Line graph of relative NOx removal efficiency over time. Figure 3 The data for are calculated based on data collected during the Catalyst Evaluation Program 2, discussed in further detail below. As shown in the figure, compared with the more catalytically active components and the use of TiO 2 and auxiliary materials (SiO 2 ) as a support material, compared with catalysts with fewer catalytically active components and using TiO 2 The relative NOx removal efficiency of the catalyst as a support material decreases at a faster rate over time.
[0084] Figure 4 According to an embodiment, two different catalysts are shown to react with SO 2 The bar graph of the initial deactivation rate over time. As shown in the figure, compared with the more catalytically active components and the use of TiO 2 and auxiliary materials (SiO 2 ) as a support material, compared with catalysts with fewer catalytically active components and using TiO 2 The initial deactivation of the catalyst as a support material is greater. In some embodiments, when SO 2 In the presence of NH 3 When tested in the selective catalytic reduction of NOx, the catalyst with less catalytically active components and TiO 2 Compared with catalysts with more catalytically active components and using TiO as a support material 2-SiO 2 The catalyst as a support material has a reduced initial deactivation rate.
[0085] Figure 5 According to the embodiment, various carrier materials and TiO 2 The X-ray diffraction measurement method is discussed in further detail in the Test Methods section below.
[0086] The peak representing anatase crystals generally appears in the range of 2θ = 24.7° to 2θ = 25.7°. Figure 5 As shown, according to peak 502, TiO 2 (Standard sample, M311 Hombikat TiO 2 ) has high crystallinity of anatase titanium dioxide. In addition, according to peaks 504 and 506, TiO 2 -SiO 2 and 20% V 2 O 5 -TiO 2 -SiO 2 (Catalyst Sample 4) The samples all have highly crystallized anatase-type titanium dioxide. The intensity (au) of peak 502 indicating anatase crystalline titanium dioxide in the standard sample is 2177. The intensity (au) of peak 506 indicating anatase crystalline titanium dioxide in catalyst sample 4 is 1988. The ratio of the intensity [Ia] of peak 506 indicating anatase crystals in the catalyst sample to the intensity [Ib] of peak 502 indicating anatase crystals in the standard sample is 91.3%.
[0087] In some embodiments, the support material may have a thickness of about 10 m 2 / g to about 3000m 2 / g, about 15m 2 / g to about 2500m 2 / g, about 20m 2 / g to about 2000m 2 / g, about 25m 2 / g to about 1500m 2 / g, about 30m 2 / g to about 1000m 2 / g, about 35m 2 / g to about 800m 2 / g, about 40m 2 / g to about 600m 2 / g, about 45m 2 / g to about 500m 2 / g, about 50m 2 / g to about 400m2 / g, about 55m 2 / g to about 350m 2 / g, or may have a specific surface area within these ranges. In some embodiments, the support material may have a specific surface area of about 60 m 2 / g to about 340m 2 / g, about 65m 2 / g to about 330m 2 / g, about 70m 2 / g to about 320m 2 / g, or about 75m 2 / g to about 310m 2 In one exemplary embodiment, the support material may have a specific surface area of about 50 m 2 / g to about 500m 2 / g specific surface area.
[0088] In some embodiments, the support material may include particles having an average diameter of about 0.5 μm to about 1000 μm, about 0.6 μm to about 900 μm, about 0.7 μm to about 800 μm, about 0.8 μm to about 700 μm, about 0.9 μm to about 600 μm, about 1.0 μm to about 500 μm, about 1.1 μm to about 400 μm, about 1.2 μm to about 300 μm, about 1.3 μm to about 200 μm, about 1.4 μm to about 100 μm, or may include particles having an average diameter within these ranges. In some embodiments, the support material 106 may include particles having an average diameter of about 1.5 μm to about 90 μm, about 1.6 μm to about 80 μm, about 1.7 μm to about 70 μm, about 1.8 μm to about 60 μm, about 1.9 μm to about 55 μm, or about 1.95 μm to about 54 μm. In one exemplary embodiment, the support material may include particles having an average diameter of about 2.0 μm to about 52 μm. In one exemplary embodiment, the support material may include particles having an average diameter of about 0.5 μm to about 1000 μm.
[0089] In some embodiments, the catalytically active component may have a loading weight percentage of about 4 wt % to about 50 wt %, about 5 wt % to about 45 wt %, about 6 wt % to about 40 wt %, about 7 wt % to about 35 wt %, about 8 wt % to about 32.5 wt %, about 9 wt % to about 30 wt %, about 10 wt % to about 27.5 wt %, about 11 wt % to about 25 wt %, about 12 wt % to about 22.5 wt %, about 15 wt % to about 20 wt %, based on the total weight of the catalyst. In yet another embodiment, the catalytically active component has a loading weight percentage of 10% to 30% based on the total weight of the catalyst.
[0090] As mentioned above, Figure 1-4 As shown, compared with the catalytic active components with lower loading wt.% and only TiO 2 The DeNOx catalyst according to the present disclosure exhibits higher SO by having a lower initial deactivation rate compared to the catalyst as a support material. 2 In one exemplary embodiment, the DeNOx catalyst includes V as a catalytically active component. 2 O 5 , and TiO as a support material 2 and SiO 2 .like Figure 5 As shown, the intensity of the anatase peak 506 of the catalyst sample 4 is substantially the same as that of the anatase peak 502 of the standard sample (e.g., 91.3%). In addition, the peak 506 also maintains the full width at half maximum (FWHM), indicating that the TiO in the catalyst sample 4 is 2 Without wishing to be bound by theory, it is assumed that the TiO 2 The reason why the crystal structure of SiO has not changed is that 2 The locations of the TiO2 are mainly on the outer surface or in the pores, rather than on the atomic level. 2 mix.
[0091] The catalytic product may include the above-mentioned catalyst, and may further include at least one additional material. The additional material is not limited to any particular type of material, and may be, for example, a membrane, a felt pad, a ceramic substrate (including but not limited to a ceramic tube), a honeycomb substrate, a monolithic substrate, or any combination thereof. In some non-limiting examples, the catalytic composite product may be a porous catalytic membrane. For example, the catalytic product may include a catalyst having a NOx removal efficiency of about 20% to about 99%. In some embodiments, the method of the catalytic reaction includes contacting a reactant stream with the above-mentioned catalyst. For the above-mentioned catalyst or a catalytic product including the catalyst, the NOx removal efficiency may be about 10% to about 99%.
[0092] Figure 6-7 The method shown is an example of various features of the method of making and / or using the catalyst, and although the combination of these illustrated features is clearly within the scope of the invention, the example and its schematic diagram do not mean that the inventive concept provided herein is limited to fewer features, additional features or Figure 6-7 Limitations of alternative features to one or more of these features are shown.
[0093] In addition, one or more steps of the following method may be optional and / or may be improved by one or more steps of other embodiments described herein. In addition, one or more steps of other embodiments described herein may be added to the method.
[0094] Figure 6 is a flow chart illustrating a method 600 of reducing the amount of a compound in a gas stream, according to one embodiment.
[0095] In step 602, method 600 may optionally include adding an auxiliary material to the support material. In some embodiments, adding an auxiliary material to the support material can maintain the TiO 2 The crystal structures are basically the same.
[0096] In step 604, method 600 may include mixing a dry catalyst precursor with a dry support material to form a mixture. In some embodiments, the dry catalyst precursor may include a metal and a ligand. In some embodiments, the catalyst precursor may not contain any aqueous liquid or any organic liquid. In some embodiments, the catalyst precursor may not contain any aqueous liquid or any organic liquid.
[0097] In some embodiments, the dry support material may include TiO having an anatase phase. 2 In some embodiments, the dry support material is prepared by adding TiO 2 Mixed with auxiliary materials to form a TiO 2 With the support material, the TiO 2 With a crystal structure having anatase phase; wherein the auxiliary material is selected from SiO 2 ,Fe 2 O 3 ,CrO 3 ,Re 2 O 7 ,Nb 2 O 5 ,K 2 O,MoO 3 ,WO 3 and Al 2 O 3 At least one of .
[0098] In some embodiments, the dry catalyst precursor may include a metal and a ligand. In some embodiments, the metal may be selected from one or more of a transition metal, a lanthanide, an alkali metal or an alkaline earth metal, or a salt thereof. In some embodiments, the metal may be selected from elements of Groups 3-14 of the Periodic Table of Elements, such as V, Cr, Mn, Ce, Fe, Cu, Zn, Sn, Ta, Ni, Co, Nb, Sb, La, Eu, Gd.
[0099] In an exemplary embodiment, the metal is selected from the group consisting of vanadium, copper, iron, molybdenum, or mixtures thereof.
[0100] In some embodiments, the ligand can be a carbonyl, oxalate, ammonium, dimethylamino, bromide, chloride, cyclopentadienyl, diketonate, or a ligand of formula (I):
[0101]
[0102] wherein R1 and R2 are each independently alkyl, substituted alkyl, aryl, substituted aryl, acyl and substituted acyl.
[0103] In an exemplary embodiment, the catalyst precursor may include a metal and an acetylacetonate group or a ketone group. For example, the precursor may include zinc(II)bis(2,2,6,6,-tetramethyl-3,5-heptanedione), di(acetylacetonato)dioxomolybdenum(VI), chromium(III)acetylacetonate, chromium(III)tris(2,2,6,6-tetramethyl-3,5-heptanedione), cobalt(II)hexafluoroacetylacetonate hydrate, copper(2,2,6,6-tetramethyl-3,5-heptanedione), copper(6,6,7,7,8,8,8-heptafluoro-2,2-dimethyl-3,5-octanedionate), copper(II)acetylacetonate. (II), copper (II) ethyl acetylacetonate, copper (II) hexafluoroacetylacetonate hydrate, copper (II) trifluoroacetylacetonate, europium (III) acetylacetonate hydrate, gadolinium (III) acetylacetonate hydrate, iron (III) acetylacetonate, lithium acetylacetonate, manganese (II) acetylacetonate, nickel (II) acetylacetonate, bis (2,2,6,6-tetramethyl-3,5-heptanedione) nickel (II), nickel (II) hexafluoroacetylacetonate hydrate, vanadyl acetylacetonate, vanadium (III) acetylacetonate or zinc acetylacetonate hydrate.
[0104] In an exemplary embodiment, the catalyst precursor is selected from the group consisting of vanadyl acetylacetonate, vanadium (III) acetylacetonate, bis (acetylacetonato) dioxymolybdenum (VI), iron (III) acetylacetonate, and copper (II) acetylacetonate.
[0105] In some embodiments, step 604 can be performed using a vortex mixer, an oscillating mixer, a double cone mixer, or a combination thereof. In some embodiments, step 604 can be performed in a scintillation vial by manual shaking. Other mixing devices are also obviously suitable. In some embodiments, step 604 can be performed under inert, dry or ambient conditions, e.g., in the absence of O 2 , there is dry N 2 is carried out under the circumstances.
[0106] In some embodiments, step 604 can be performed for about 30 seconds to about 10 hours, about 35 seconds to about 9.5 hours, about 40 seconds to about 9 hours, about 45 seconds to about 8.5 hours, about 50 seconds to about 8 hours, about 55 seconds to about 7.5 hours, about 1 minute to about 7 hours, about 1.5 minutes to about 6.5 hours, about 2.5 minutes to about 5.5 hours, about 3 minutes to about 5 hours, or a period of time included in these ranges. In some embodiments, step 604 can be performed for about 30 seconds to about 4.5 hours, about 40 seconds to about 4 hours, or about 50 seconds to about 3.5 hours. In an exemplary embodiment, step 604 can be performed for about 1 minute.
[0107] In step 606, method 600 may include calcining the mixture to form a supported catalyst. Calcination step 606 may include heat treating the dry mixture formed in step 604. Calcination step 606 may be performed using standard calcination equipment, such as a rotary calciner. In some embodiments, mixing step 604 and calcination step 606 may be performed simultaneously (i.e., combined into one step). In some embodiments, mixing step 604 and calcination step 606 may be performed continuously.
[0108] In some embodiments, the calcining step 606 can be performed using a rapid heating method (e.g., heating the dry mixture in an aluminum pan placed on a preheated hot plate). In some embodiments, the calcining step 606 can be performed using a slow heating method (e.g., slowly heating the dry mixture from room temperature in a crucible placed in a muffle furnace). In some embodiments, the heating can be performed by placing the mixture in a preheated oven.
[0109] In some embodiments, the dry mixture may be calcined at about 100°C to about 500°C, about 105°C to about 480°C, about 110°C to about 460°C, about 115°C to about 440°C, about 120°C to about 430°C, about 125°C to about 420°C, about 130°C to about 410°C, about 135°C to about 400°C, about 140°C to about 390°C, about 145°C to about 380°C, or at a temperature included in these ranges. In some embodiments, the dry mixture may be calcined at a temperature of about 146°C to about 375°C, about 147°C to about 370°C, or about 148°C to about 365°C. In an exemplary embodiment, the dry mixture may be calcined at a temperature of about 360°C.
[0110] In some embodiments, the dry mixture may be calcined at a rate of about 1°C / min to about 50°C / min, about 1.25°C / min to about 45°C / min, about 1.5°C / min to about 40°C / min, about 1.75°C / min to about 35°C / min, about 2°C / min to about 30°C / min, about 2.25°C / min to about 25°C / min, about 2.5°C / min to about 20°C / min, about 2.75°C / min to about 15°C / min, about 3°C / min to about 10°C / min, or at a rate included in these ranges. In some embodiments, the dry mixture may be calcined at a rate of about 3.2°C / min to about 9°C / min, about 3.4°C / min to about 8°C / min, about 3.6°C / min to about 7°C / min, or about 3.8°C / min to about 6°C / min. In an exemplary embodiment, the dry mixture may be calcined at a rate of about 4°C / min to about 5°C / min.
[0111] In some embodiments, the dry mixture is calcined in an atmosphere containing about 1 to about 25% oxygen by volume, about 2 to about 20% oxygen by volume, about 3 to about 15% oxygen by volume, about 3.5 to about 10% oxygen by volume, about 4 to about 9% oxygen by volume, about 4.5 to about 8% oxygen by volume, about 5 to about 7% oxygen by volume, about 5.5 to about 6.5% oxygen by volume, or oxygen by volume within these ranges. In an exemplary embodiment, the dry mixture can be calcined in an atmosphere containing about 21% oxygen by volume.
[0112] In an exemplary embodiment, the dry catalyst precursor may be vanadyl acetylacetonate or vanadium (III) acetylacetonate, and the support material may be TiO 2 -SiO 2 , and the calcination can be performed at a temperature of about 360°C.
[0113] Catalyst can be prepared by steps 604, 606 and optional 602 in method 600. In some embodiments, the catalyst has a certain metal content (wt%), based on the gross weight of the catalyst. In some embodiments, the metal content of the catalyst is from about 0.1 wt % to about 50 wt %, from about 0.25 wt % to about 45 wt %, from about 0.5 wt % to about 40 wt %, from about 1 wt % to about 35 wt %, from about 1.5 wt % to about 32.5 wt %, from about 2.0 wt % to about 25 wt %, from about 2.25 wt % to about 27.5 wt %, from about 2.5 wt % to about 25 wt %, from about 2.75 wt % to about 22.5 wt %, from about 3.0 wt % to about 20 wt %, or a metal content (wt %) included in these ranges. In some embodiments, the metal content of the catalyst is from about 3.2 wt % to about 19 wt %, from about 3.4 wt % to about 18 wt %, from about 3.6 wt % to about 17 wt %, from about 3.8 wt % to about 16 wt %. In some embodiments, the metal content of the catalyst is from about 4 wt % to about 50 wt %. In some embodiments, the metal content of the catalyst is about 20 wt %.
[0114] In some embodiments, the catalyst has a NOx removal efficiency of about 1% to about 99%, about 5% to about 90%, about 10% to about 80%, about 15% to about 70%, about 20% to about 60%, or NOx removal efficiencies included in these ranges.
[0115] In step 608, method 600 may include providing a first gas stream including a concentration of a compound. In step 610, method 600 may include contacting the gas stream with the catalyst formed at step 606 to form a second gas stream having a second concentration of the compound. In some embodiments, method 600 may include contacting the gas stream with the catalytic article formed at step 606 to form a second gas stream having a second concentration of the compound. In an exemplary embodiment, the compound may include NOx, including, for example, nitric oxide (NO) and / or nitrogen dioxide (NO 2 The compound may also include nitrogen (N 2 ), dioxins or dioxin-like compounds, halogens or halogenated compounds. In some examples, the first gas stream may also include oxygen (O 2 ), water (H 2 O), carbon monoxide (CO), carbon dioxide (CO 2 ), sulfur dioxide (SO 2 ), sulfur trioxide (SO 3), hydrocarbons, or at least one of one or more organic or inorganic materials, etc. In an exemplary embodiment, the gas stream is a flue gas stream having a temperature of 140-250°C.
[0116] In some embodiments, a first gas stream having a first concentration of the compound is located upstream and a second gas stream having a second concentration of the compound is located downstream. In some embodiments, the first concentration is greater than the second concentration.
[0117] The first gas stream may include SO at a concentration of about 1 to 200 ppm, about 10 to 180 ppm, about 20 to 160 ppm, about 30 to 140 ppm, about 40 to 120 ppm, or about 50 to 100 ppm. 2 .
[0118] In some embodiments, in step 612a, the above-mentioned compounds may include NOx, and method 600 may optionally include adding ammonia (NH4) in a concentration range of 0.0001% to 0.5% of the flue gas flow concentration. 3 ).
[0119] In some embodiments, the catalytic product is increased in NO x The removal efficiency includes adding ammonia at a concentration of 0.0001% to 0.5% of the flue gas stream concentration. In some embodiments, increasing the NO x The removal efficiency includes adding ammonia at a concentration of 0.001% to 0.5% of the flue gas stream concentration. In some embodiments, increasing the NO x The removal efficiency includes adding ammonia at a concentration of 0.01% to 0.5% of the flue gas stream concentration. In some embodiments, increasing the NO x Removal efficiencies include addition of ammonia at concentrations of 0.1% to 0.5% of the flue gas stream concentration.
[0120] In some embodiments, the catalytic product is increased in NO x The removal efficiency includes adding ammonia at a concentration of 0.0001% to 0.1% of the flue gas stream concentration. In some embodiments, increasing the NO x The removal efficiency includes adding ammonia at a concentration of 0.0001% to 0.05% of the flue gas stream concentration. In some embodiments, increasing the NO x Removal efficiencies include addition of ammonia at concentrations of 0.0001% to 0.005% of the flue gas stream concentration.
[0121] In some embodiments, the catalytic product is increased in NO xThe removal efficiency includes adding ammonia at a concentration of 0.005% to 0.1% of the flue gas stream concentration. In some embodiments, increasing the NO x Removal efficiencies include addition of ammonia at concentrations of 0.005% to 0.05% of the flue gas stream concentration.
[0122] In a subsequent step 614a, method 600 may optionally include increasing the temperature of the flue gas stream to a temperature between 240°C and 280°C.
[0123] Alternatively, in step 612b, method 600 may optionally include introducing additional NO into the flue gas stream. 2 , change NO 2 The concentration is increased to between 2% and 99% of the total NOx concentration in the first gas stream.
[0124] Performing optional steps 612a, 614a, and 612b may increase the compound removal efficiency of the catalytic article, thereby regenerating the catalyst.
[0125] Figure 7 is a flow chart illustrating a method of reducing the amount of a compound in a gas stream, according to an embodiment.
[0126] In step 702, method 700 may include mixing a dry catalyst precursor with a dry support material to form a mixture. In some embodiments, the dry catalyst precursor may include a metal and a ligand. In some embodiments, the catalyst precursor may not contain any aqueous liquid or any organic liquid. In some embodiments, the catalyst precursor may not contain any aqueous liquid or any organic liquid.
[0127] In some embodiments, the dry catalyst precursor may include a metal and a ligand. In some embodiments, the metal may be selected from elements of Groups 3-14 of the periodic table, such as V, Cr, Mn, Ce, Fe, Cu, Zn, Sn, Ta, Ni, Co, Nb, Sb, La, Eu, Gd. In an exemplary embodiment, the metal is selected from the group consisting of vanadium, copper, iron, molybdenum, or mixtures thereof.
[0128] In some embodiments, the dry support material may include TiO having an anatase phase. 2 The dry support material may optionally include auxiliary materials. In some embodiments, the dry support material is prepared by 2 Mixed with auxiliary materials to form a TiO 2 With the support material, the TiO 2 With a crystal structure having anatase phase; wherein the auxiliary material is selected from SiO 2 ,Fe 2 O 3,CrO 3 ,Re 2 O 7 ,Nb 2 O 5 ,K 2 O,MoO 3 ,WO 3 and Al 2 O 3 In some embodiments, the dry support material may be TiO 2 and commercially available mixtures of auxiliary materials.
[0129] In step 704, method 700 may include calcining the mixture to form a supported catalyst. Calcination step 704 may include heat treating the dry mixture formed in step 702. Calcination step 704 may be performed using standard calcination equipment, such as a rotary calciner. In some embodiments, mixing step 702 and calcination step 704 may be performed simultaneously (i.e., combined into one step). In some embodiments, mixing step 702 and calcination step 704 may be performed continuously.
[0130] In some embodiments, the calcining step 704 can be performed using a rapid heating method (e.g., heating the dry mixture in an aluminum pan placed on a preheated hot plate). In some embodiments, the calcining step 704 can be performed using a slow heating method (e.g., slowly heating the dry mixture from room temperature in a crucible placed in a muffle furnace). In some embodiments, the heating can be performed by placing the mixture in a preheated oven.
[0131] In some embodiments, the method 700 may optionally include step 706. In optional step 706, the method 700 may include adding an auxiliary material to the support material, wherein the support material includes TiO having an anatase phase. 2 In some embodiments, optional step 706 includes adding auxiliary materials to the support material so that TiO 2 The crystal structure of the 2 , Fe 2 O 3 CrO 3 、Re 2 O 7 , Nb 2 O 5 , K 2 O、MoO 3 , WO 3 、Al 2 O 3 and at least one of zeolite.
[0132] In step 708, method 700 may include providing a first gas stream including a certain concentration of a compound. In step 710, method 700 may include contacting the gas stream with a catalyst to form a second gas stream having a second concentration of the compound. In some embodiments, method 700 may include contacting the gas stream with a catalytic article to form a second gas stream having a second concentration of the compound. In an exemplary embodiment, the compound may include NOx, including, for example, nitric oxide (NO) and / or nitrogen dioxide (NO 2 The compound may also include nitrogen (N 2 ), dioxins or dioxin-like compounds, halogens or halogenated compounds. In some examples, the first gas stream may also include oxygen (O 2 ), water (H 2 O), carbon monoxide (CO), carbon dioxide (CO 2 ), sulfur dioxide (SO 2 ), sulfur trioxide (SO 3 ), hydrocarbons, or at least one of one or more organic or inorganic materials, etc. In an exemplary embodiment, the gas stream is a flue gas stream having a temperature of 140-250°C.
[0133] In some embodiments, a first gas stream having a first concentration of the compound is located upstream and a second gas stream having a second concentration of the compound is located downstream. In some embodiments, the first concentration is greater than the second concentration.
[0134] Test Method
[0135] It should be understood that although certain methods and apparatus are described below, other methods or apparatuses determined to be suitable by one of ordinary skill in the art may alternatively be used.
[0136] Catalyst Evaluation Procedure 1 – Catalyst Powder Performance Testing for NOx Removal
[0137] The following procedure was used to test the NOx removal performance of the catalyst. The NOx removal reaction of the catalyst powder thus prepared was carried out in a fixed bed quartz flow reactor at different temperatures. 0.1 g of catalyst powder was used in the test. The feed gas mixture contained 100 ppm NO, 20 ppm NO 2 、105ppm NH 3 、6vol.%O 2 and the remainder N 2 The NOx removal reaction was measured at a total flow rate of 0.45 L / min. x Removal efficiency, using MKS MULTI-GAS TMA 2030D FTIR analyzer (MKS Instruments, Andover, MA) monitored the upstream NOx concentration (i.e., NO entering the chamber before exposure to the catalyst powder). x concentration) and downstream NOx concentration.
[0138] The NOx removal efficiency (i.e., "DeNOx efficiency (%)") was calculated according to the following formula:
[0139] DeNO x Efficiency (%) = (NO x入 –NO x出 ) / NO x入 ×100%.
[0140] Where NOx = NO and NO in the gas flow 2 Total concentration
[0141] NO x入 = Upstream concentration of NOx
[0142] NO x出 = Downstream concentration of NOx
[0143] The apparent reaction rate constant (k m ) is calculated according to the following formula:
[0144]
[0145] where k m = first-order apparent reaction rate involving catalyst mass (cm 3 / gs)
[0146] v = gas flow rate under reaction conditions (cm 3 / s)
[0147] W = catalyst mass (g)
[0148] Catalyst Evaluation Procedure 2 – Using SO 2 Catalyst powder performance test
[0149] The following procedure was used to test exposure to SO 2 The NOx removal performance of the catalyst is 2 Under exposure conditions, the prepared catalyst powder was subjected to NOx removal reaction in a fixed bed quartz flow reactor at 220°C. During the test, 0.1 g of catalyst powder was mixed with 0.5 g of silicon carbide (Sigma Aldrich). The feed gas mixture contained 200 ppm NO, 9 ppm NO 2 、200ppm NH 3 、6vol.%O 2 , 5vol% water and the balance N2 The NOx removal reaction was measured at a total flow rate of 0.8 L / min. x Removal efficiency, using MKS MULTI-GAS TM A 2030D FTIR analyzer (MKS Instruments, Andover, MA) monitored the upstream NOx concentration (i.e., NO entering the chamber before exposure to the catalyst powder). x The NOx removal efficiency is calculated according to the following formula:
[0150] DeNO x Efficiency (%) = (NO x入 –NO x出 ) / NO x入 ×100%.
[0151] Where NOx = NO and NO in the gas flow 2 Total concentration
[0152] NO x入 = Upstream concentration of NOx
[0153] NO x出 = Downstream concentration of NOx
[0154] The relative DeNOx efficiency is calculated according to the following formula:
[0155]
[0156] The initial inactivation rate in the first 21 hours was calculated according to the following formula:
[0157]
[0158] X-ray diffraction measurements
[0159] X-ray diffraction measurements were performed on a Rigaku SmartLab high-resolution X-ray diffractometer with a Cu KαCu Kα (40 kV / 45 mA) source. The incident optics used were parallel beam crossed beam optics (5° Soller slit, 1.0 mm divergence slit, 10 mm length limiting slit). The receiving optics were nickel filters for Cu Kβ (5° Soller slit, 2.0- and 2.1-mm receiving slits, HyPix 3000 detector operated in zero D continuous mode). The scan was set to 10–60° 2θ range, 0.02° increments, 2.0° / min. The powder was placed in a 20 x 20 x 0.5 mm hole in a glass plate. Sufficient powder was used to fill the entire hole volume and flattened with a glass spacer. Excess powder was scraped off with a scraper.
[0160] Example
[0161] Example 1 - Preparation of Catalyst Sample 1
[0162] 0.116 g of vanadyl acetylacetonate (Sigma-Aldrich) was added to 0.36 g of TiO 2 (Hombikat M311, specific surface area is about 304m 2 / g) and placed in a scintillation vial to prepare 10wt.% V 2 O 5 -TiO 2 Catalyst powders. The two dry powders were mixed by shaking on a vortex mixer (Cole-Parmer) for 1 minute. The powder mixture was then transferred to an aluminum weighing dish and heat treated at 300°C for 3 hours at a heating rate of 5°C / min.
[0163] Example 2 - Preparation of Catalyst Sample 2
[0164] 0.116 g of vanadyl acetylacetonate (Sigma-Aldrich) was added to 0.36 g of TiO 2 -SiO 2 (Hombikat M411-10%SiO 2 , with a specific surface area of about 291m 2 / g) and placed in a scintillation vial to prepare 10wt.% V 2 O 5 -TiO 2 -SiO 2 Catalyst powders. The two dry powders were mixed by shaking on a vortex mixer (Cole-Parmer) for 1 minute. The powder mixture was then transferred to an aluminum weighing dish and heat treated at 360°C for 3 hours at a heating rate of 5°C / min.
[0165] Example 3 - Preparation of Catalyst Sample 3
[0166] 0.167 g of vanadyl acetylacetonate (Sigma-Aldrich) was added to 0.344 g of TiO 2 -SiO 2 (Hombikat M411-10% SiO 2 , with a specific surface area of about 291m 2 / g) and placed in a scintillation vial to prepare 15wt.% V 2 O 5 -TiO 2 -SiO 2Catalyst powders. The two dry powders were mixed by shaking on a vortex mixer (Cole-Parmer) for 1 minute. The powder mixture was then transferred to an aluminum weighing dish and heat treated at 360°C for 3 hours at a heating rate of 5°C / min.
[0167] Example 4 - Preparation of Catalyst Sample 4
[0168] 0.233 g of vanadyl acetylacetonate (Sigma-Aldrich) was added to 0.32 g of TiO 2 -SiO 2 (Hombikat M411-10%SiO 2 , with a specific surface area of about 291m 2 / g) and placed in a scintillation vial to prepare 20wt.% V 2 O 5 -TiO 2 -SiO 2 Catalyst powders. The two dry powders were mixed by shaking on a vortex mixer (Cole-Parmer) for 1 minute. The powder mixture was then transferred to an aluminum weighing dish and heat treated at 360°C for 3 hours at a heating rate of 5°C / min.
[0169] The invention of the present application has been described above in general terms and in conjunction with specific embodiments. It will be apparent to those skilled in the art that various modifications and variations may be made to the embodiments described herein without departing from the spirit and scope of the present invention. Therefore, the embodiments are intended to cover such modifications and variations of the present invention as long as such modifications and variations are within the scope of the appended claims and their equivalents.
Claims
1. A catalyst comprising: Catalytically active components; and A support material comprising TiO2 having a crystal structure comprising an anatase phase; The carrier material includes auxiliary materials.
2. The catalyst as claimed in claim 1, wherein the auxiliary material is selected from at least one of SiO2, MoO3, WO3 and Al2O3.
3. The catalyst as claimed in claims 1-2, wherein the weight percentage of the auxiliary material is 2% to 35%, based on the total weight of the catalyst.
4. The catalyst according to claims 1-3, wherein the auxiliary material is SiO2.
5. The catalyst as described in claims 1-4, wherein the peak intensity ratio [(Ia / Ib)×100] is 30% to 360%, and the peak intensity ratio [(Ia / Ib)×100] represents the ratio of the peak intensity [Ia] of anatase crystals existing in the range of 2θ=24.7° to 2θ=25.7° of the powder X-ray diffraction of TiO2 to the peak intensity [Ib] of anatase existing in the range of 2θ=24.7° to 2θ=25.7° of the powder X-ray diffraction of a standard sample of titanium dioxide composed of anatase.
6. The catalyst according to claims 1 to 5, wherein The catalyst has a NOx removal efficiency of 30% to 90% in a temperature range of 150°C to 280°C.
7. The catalyst according to claim 6, wherein The catalyst has a temperature range of 40 to 400 cm 3 / gs for the selective catalytic reduction of NOx with NH3.
8. The catalyst of claims 1-7, wherein the catalyst has a NOx removal efficiency of 60% to 80% in a temperature range of 170°C to 220°C.
9. The catalyst according to claims 1 to 8, wherein When tested for the selective catalytic reduction of NOx with NH3 in the presence of SO2, the catalyst has a reduced initial deactivation rate compared to a catalyst comprising a support material composed of TiO2.
10. The catalyst according to claims 1 to 9, wherein The specific surface area of the carrier material is 50 to 500 m 2 / g.
11. The catalyst of claims 1-10, wherein the catalytically active component comprises at least one of the following groups: vanadium monoxide (VO), vanadium trioxide (V2O3), vanadium dioxide (VO2), vanadium pentoxide (V2O5), molybdenum trioxide (MoO3), manganese oxide (MnO2), iron (III) oxide (Fe2O3), iron (II) oxide (FeO), copper oxide (CuO) or any combination thereof.
12. The catalyst according to claims 1 to 11, wherein The loading weight percentage of the catalytically active component is 4% to 50%, based on the total weight of the catalyst.
13. The catalyst according to claims 1 to 12, wherein The loading weight percentage of the catalytically active component is 10% to 30% based on the total weight of the catalyst.
14. The catalyst of claims 1-13, wherein the support material comprises particles having an average diameter of 0.5 μm to 1000 μm.
15. The catalyst according to claims 1 to 14, wherein The catalytically active component is V2O5, the carrier material is TiO2, and the auxiliary material is SiO2.
16. Catalyzed article comprising the catalyst of claims 1-15.
17. A method of catalyzing a reaction, the method comprising contacting a reactant stream with the catalyst of claims 1-15.
18. The catalyst of claims 1 to 15 or the catalytic product of claim 16, wherein: The catalyst or catalytic article has a NOx removal efficiency of 10% to 99% in a temperature range of 150°C to 280°C.
19. A method of reducing the amount of a chemical compound from a gas stream, comprising: providing a first gas stream comprising a first concentration of a compound; and contacting the gas stream with the catalytic article of claim 16 to form a second gas stream comprising a second concentration of the compound; Wherein, the first concentration is greater than the second concentration.
20. The method of claim 19, wherein the first gas stream comprises SO2 at a concentration of 1 to 200 ppm.
21. The method of claims 19-20, wherein: The compounds include NOx.
22. The method of claims 19-21, wherein the compound comprises at least one of nitrogen (N2), dioxin or dioxin-like compounds, halogens or halogenated compounds.
23. The method of claims 19-22, wherein: The first gas flow also includes at least one of oxygen (O2), water (H2O), carbon monoxide (CO), carbon dioxide (CO2), sulfur dioxide (SO2), sulfur trioxide (SO3), hydrocarbons, or one or more organic or inorganic materials.
24. The method of claims 19-23, wherein: The gas stream is a flue gas stream having a temperature of 140 to 280°C.
25. The method of claim 24, further comprising: Increasing the compound removal efficiency of the catalytic article, comprising: adding ammonia (NH3) at a concentration of 0.0001% to 0.5% of the flue gas stream concentration; and Increasing the temperature of the flue gas flow to 240°C-280°C; Wherein the compound is NOx.
26. The method of claim 24, further comprising: Increasing the compound removal efficiency of the catalytic article, comprising: By introducing additional NO2 into the flue gas stream, the NO2 concentration is increased to the NO in the first gas stream. x 2% to 99% of total concentration.
27. A method for preparing a catalyst, the method comprising: mixing a catalyst precursor comprising a metal and a ligand with a support material to form a mixture, the support material comprising TiO2; calcining the mixture; and Auxiliary materials are added to the support material so that the crystal structure of TiO2 remains substantially unchanged.
28. The method of claim 27, wherein the metal is selected from one or more of a transition metal, an alkali metal or an alkaline earth metal, or a salt thereof.
29. The method of claims 27-28, wherein the metal is selected from the group consisting of vanadium, molybdenum, copper, iron or mixtures thereof.
30. The method of claims 27-29, wherein the ligand is a carbonyl, oxalate, ammonium, cyclopentadienyl, diketonate, or a ligand of formula I: wherein R1 and R2 are each independently alkyl, substituted alkyl, aryl, substituted aryl, acyl and substituted acyl.
31. The method of claims 27-30, wherein: The catalyst precursor is selected from the group consisting of vanadium acetylacetonate, vanadium (III) acetylacetonate, bis (acetylacetonate) dioxymolybdenum (VI), iron (III) acetylacetonate and copper (II) acetylacetonate.
32. The method of claims 27-31, wherein: The metal content of the catalyst is 4 wt % to 50 wt %, based on the total weight of the catalyst.
33. A method for preparing a catalyst, the method comprising: mixing a catalyst precursor comprising a metal and a ligand with a support material to form a mixture, and calcining the mixture; The support material comprises TiO2 and an auxiliary material, and the TiO2 has a crystal structure including an anatase phase.
34. A method for preparing a catalyst, the method comprising: mixing TiO2 with an auxiliary material to form a support material comprising TiO2, wherein the TiO2 has a crystal structure including an anatase phase; mixing a catalyst precursor comprising a metal and a ligand with a support material to form a mixture; and The mixture is calcined.
35. The method of claims 27-34, wherein the auxiliary material is selected from the group consisting of SiO2, MoO3, WO3 and Al2O3.
